Fenomena Hijrah Artis dalam Perspektif Psikologi Transpersonal - Umami, Idail Uzmi Fitri (Al-Riwayah : Jurnal Kependidikan, 2019)
Nowadays, we can see in various media, especially on television, that there are lots of news about some artists who decided to change their appearance in a more religious direction, some decided to wear hijab and some let their beards grow, the changing of appearance is not without rhyme or effect. That is quite interesting to be reviewed the reason they emigrated. Some examples of artists who decide to emigrate include Teuku Wisnu, Fenita Arie, Laudya Cintya Bella and others. The average reason for them is a spiritual experience that they experience so as to create awareness in the heart. Departing from this problem, it is associated with one of the branches of the fourth school of psychology, transpersonal psychology. According to Davis, transpersonal psychology is between psychology and spiritual experience. Hence from this it is necessary to examine the phenomenon of migrating artists with transpersonal psychology.